Narrative review on sustainable feedback compared to other concepts (Revista Lusófona de Educação, 2025)
The text addresses the ambiguity in the terminology of teacher feedback practices and the importance of understanding these variations. Formative feedback aims to help students understand their learning process and choose appropriate strategies. The concept of Sustainable Feedback (SFB) emphasizes dialogical and enduring interactions, with a focus on active student participation. The study aims to identify articles that mention SFB, analyze the theoretical approach of the authors, assess the importance of SFB characteristics, and compare discourses with and without mention of SFB. Despite different terminologies, there are similarities in the characteristics of effective feedback practices and the concept of sustainable feedback.